Muslim-Christian polemics in Safavid Iran - Tiburcio, Alberto (Edinburgh historical studies of Iran and the Persian world., 2020)
This book explores the history of Muslim-Christian theological exchanges in Iran during the 17th and early 18th centuries. Focused on the work of the renegade missionary 'Ali Quli Jadid al-Islam (d. 1734), it contributes to ongoing debates on the nature of confessionalism, interreligious encounters, and cultural translation in early modern Muslim empires. By disentangling the connections between polemics and other forms of Islamic learning and by emphasizing the Shi'i character of the case in question, this study accounts for the dynamism of polemics as an ever-evolving genre capable to adapt to different historical contexts.